2011
DOI: 10.1056/nejmoa1001689
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Efflux Capacity, High-Density Lipoprotein Function, and Atherosclerosis

Abstract: BACKGROUND High-density lipoprotein (HDL) may provide cardiovascular protection by promoting reverse cholesterol transport from macrophages. We hypothesized that the capacity of HDL to accept cholesterol from macrophages would serve as a predictor of atherosclerotic burden. METHODS We measured cholesterol efflux capacity in 203 healthy volunteers who underwent assessment of carotid artery intima–media thickness, 442 patients with angiographically confirmed coronary artery disease, and 351 patients without su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

56
1,256
13
18

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,718 publications
(1,343 citation statements)
references
References 38 publications
56
1,256
13
18
Order By: Relevance
“…Using unsupervised hierarchical clustering, we noted that the BHK‐stimulated assay clustered with the J774‐basal model in controls, but with the J774‐stimulated and J774‐ABCA1–dependent measures in cases (Figure 1). Finally, we confirmed that CECs were associated with reduced prevalent CAD events, thus replicating previous observations3 and validating our data set (Table 1). …”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Using unsupervised hierarchical clustering, we noted that the BHK‐stimulated assay clustered with the J774‐basal model in controls, but with the J774‐stimulated and J774‐ABCA1–dependent measures in cases (Figure 1). Finally, we confirmed that CECs were associated with reduced prevalent CAD events, thus replicating previous observations3 and validating our data set (Table 1). …”
Section: Resultssupporting
confidence: 91%
“…Background cholesterol efflux (obtained in the absence of apolipoprotein B–depleted plasma) was subtracted from individual cholesterol efflux values. To correct for interassay variability, CEC was measured with the same pool of 40 healthy volunteers’ serum in each assay, and individual percentage CEC values were divided (normalized) by percentage CEC of control serum in each assay, as described previously 3, 5. Control serum CEC values were required to be within the limits defined by the historical mean of CEC for each model, plus or minus 2 SDs, to allow batch qualification.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As HDL cholesterol concentrations were found predictive for HF exacerbations independent of HF aetiology,5 increasing research has focused on HDL. It has become apparent that quality and function of HDL may relate more to outcome in CV diseases than serum levels 6. Particularly, the anti‐oxidant capacity of HDL was found associated with HF and clinical outcome,7 emphasizing the pivotal role of oxidative stress in the pathogenesis of HF.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing our knowledge of this fundamental property of apoA-I has clinical significance because apoA-I plasma levels uniquely predict risk of cardiovascular disease (22)(23)(24). One pathway through which apoA-I exerts its beneficial lipid trafficking function involves the plasma membrane transporter ATP-* This work was supported by a new investigator award from the TobaccoRelated Disease Research Program of California (Grant 18KT-0021) and an International Atherosclerosis Society Visiting Fellowship Award.…”
mentioning
confidence: 99%